HUBUNGAN PIJAT OKSITOSIN TERHADAP PENURUNAN TINGGI FUNDUS UTERI PADA IBU NIFAS - Amelia Nur Hidayanti (WOMB Midwifery Journal, 2022)
Oxytocin massage is a spinal massage in which the 5-6th nerves reach the scapula to speed up the work of the parasympathetic nerves to the back of the brain so that oxytocin comes out. The pituitary gland secretes the hormone oxytocin so that it strengthens uterine contractions, blood vessel pressure and can increase the speed of uterine involution. This process can reduce bleeding and increase the speed of uterine involution. The aim of this study was to determine the relationship between oxytocin massage and a decrease in Uterine Fundal Height in postpartum women in Sukoharjo Village, Pati District, Pati Regency. Research method using cross sectional. The type of research used is an analytic survey. The research population is postpartum mothers. The sampling technique used was Stratified Random Sampling of 31 respondents. Observation results showed that there was a relationship between oxytocin massage and a decrease in Uterine Fundal Height in postpartum women in Sukoharjo Village, Pati District, Pati Regency with a p value of 0.001 <0.05. The conclusion of the study is that there is a relationship between oxytocin massage and a decrease in Uterine Fundal Height in Sukoharjo Village, Pati District, Pati Regency.